Space and Spatial Analysis in Archaeology. - Robertson, Elizabeth C. (University of Calgary Press, 2000)
Space and Spatial Analysis in Archaeology is made up of thirty-seven contributions based on and developed from papers presented at the 2001 Chacmool Conference, An Odyssey of Space, one of the first and largest meetings to focus on this increasingly important aspect of archaeological research. The papers discuss studies undertaken in a number of different archaeological settings and incorporate a broad range of methodological and theoretical approaches to spatial analysis. They reflect the roots of spatial archaeology in approaches such as settlement pattern analysis and also look at innovative new directions in the field, such as landscape archaeology and space syntax studies. This range of focus provides a valuable snapshot of the state of spatial research in archaeology as it enters the twenty-first century and reflects its increasing breadth and popularity among archaeological researchers.